The complex genetics of hypoplastic left heart syndrome - Liu, Xiaoqin; Yagi, Hisato; Saeed, Shazina; Bais, Abha S; Gabriel, George C; Chen, Zhaohan; Peterson, Kevin A; Li, You; Schwartz, Molly C; Reynolds, William T; Saydmohammed, Manush; Gibbs, Brian; et al. (Nature genetics, 2017)
Cecilia Lo and colleagues report the recovery of mice with hypoplastic left heart syndrome (HLHS) from a large mutagenesis screen. They find genetic heterogeneity among HLHS mice and functionally validate mutations in two genes, Sap130 and Pcdha , as contributing to HLHS in a combinatorial manner. Congenital heart disease (CHD) affects up to 1% of live births 1 . Although a genetic etiology is indicated by an increased recurrence risk 2 , 3 , sporadic occurrence suggests that CHD genetics is complex 4 . Here, we show that hypoplastic left heart syndrome (HLHS), a severe CHD, is multigenic and genetically heterogeneous. Using mouse forward genetics, we report what is, to our knowledge, the first isolation of HLHS mutant mice and identification of genes causing HLHS. Mutations from seven HLHS mouse lines showed multigenic enrichment in ten human chromosome regions linked to HLHS 5 , 6 , 7 . Mutations in Sap130 and Pcdha9 , genes not previously associated with CHD, were validated by CRISPR–Cas9 genome editing in mice as being digenic causes of HLHS. We also identified one subject with HLHS with SAP130 and PCDHA13 mutations. Mouse and zebrafish modeling showed that Sap130 mediates left ventricular hypoplasia, whereas Pcdha9 increases penetrance of aortic valve abnormalities, both signature HLHS defects. These findings show that HLHS can arise genetically in a combinatorial fashion, thus providing a new paradigm for the complex genetics of CHD.